Asymptotic justification of dynamical equations for generalized Marguerre–von Kármán anisotropic shallow shells. Issue 5 (4th April 2017) - Ghezal, Abderrezak; Chacha, Djamal Ahmed
Abstract : In this paper, using technics from asymptotic analysis, we show that the three-dimensional dynamical model for a non-linearly elastic shallow shell made of anisotropic material, with boundary conditions of generalized Marguerre–von Kármán's type, reduces to two-dimensional dynamical model.